The new indelible memories. - Geppert, L.
Flash is under assault by technologies bent on proving they can do better. These upstart random access memories (RAMs) have little in common. The ferroelectric memory picks up on the electric fields inside certain atoms and the directions in which they point. The magnetoresistive type stores data as the either-or directions of the alignment of small magnetic regions in a ferromagnetic material. A third, Ovonic Unified Memory, is based on a material that switches between crystalline and amorphous phases. Different as these technologies are, they share two advantages over flash. First, they can write data in a few tens of nanoseconds, like the dynamic RAMs in a computer's main memory. Second, the new memories can withstand constant rewriting.
Keywords: Ovonic Unified Memory; Amorphous phase switching; Ferroelectric memory; Magnetoresistive memory; Nanosecond access time; Random access memories; Rewriting